2021
DOI: 10.1039/d1ce00543j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding from crystalline water mediates the hydration/dehydration of mequitazine glycolate

Abstract: The structural transition behaviors of the hydration and dehydration of mequitazine glycolate (MQZ-GLC) after exposure to heat and relative humidity have yet not been clarified, although our previous study demonstrated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The conditions under which the tetrahydrate is stable are still unknown. Nucleotides are also organic crystals known to show structural changes accompanied by dehydration or hydration (Sugawara et al, 1991(Sugawara et al, , 2002Okura et al, 2021;Urabe et al, 1995). In these studies, humidity was recorded as a key parameter controlling the structure of the nucleotide hydrate crystals.…”
Section: Crystal Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions under which the tetrahydrate is stable are still unknown. Nucleotides are also organic crystals known to show structural changes accompanied by dehydration or hydration (Sugawara et al, 1991(Sugawara et al, , 2002Okura et al, 2021;Urabe et al, 1995). In these studies, humidity was recorded as a key parameter controlling the structure of the nucleotide hydrate crystals.…”
Section: Crystal Datamentioning
confidence: 99%
“…Structural information on water molecules, which are stabilized by hydrogen bonds with other molecules, is essential for studying the thermal, hygroscopic and other properties of hydrate materials. Crystallographic studies of hydrogen bonds in hydrated saccharides and other materials have been widely performed (Berman, 1970;Jeffrey & Huang, 1990;Viriyarattanasak et al, 2015;Taga et al, 1972;Sugawara et al, 1991Sugawara et al, , 2002Okura et al, 2021;Bajpai et al, 2016). Hydrogen bonds are classified as strong, moderate and weak, with mostly covalent, mostly electrostatic and electrostatic H� � �A (A is an acceptor) interactions, respectively, based on the geometrical parameters of the distances and angles between the donors (D), acceptors and H atoms of the bonds (Jeffrey, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Generally, the removal and addition of lattice solvent molecules from crystals is the most common method, which involves only intermolecular hydrogen bonding interactions rather than complex chemical reactions. 6,7 Ligand substitution is another method, which involves the exchange of substances and the breaking and generation of coordination bonds. 8,9 In addition, the realization of reversible single-crystal-to-single-crystal (SC-SC) conversions and the definite structures determined using X-ray single-crystal diffraction provide the opportunity to study structure-function relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Making sense of the dehydration mechanism is conducive to regulating dehydration behavior and obtaining the desired target product profile. Kons et al reported that quifenadine hydrochloride dihydrate reversibly dehydrated through channels and rearranged into similar packing to anhydrate form B. Okura et al have suggested that the dehydrated mequitazine glycolate would adjust conformation to fill the voids generated from removal of water of crystallization. Braun and Griesser reported that the diaminophenyl part in the lattice of the dapsone hydrate would open up to liberate water molecules in the direction that is parallel to (011).…”
Section: Introductionmentioning
confidence: 99%